WRKY genes provide novel insights into their role against Ralstonia solanacearum infection in cultivated peanut (Arachis hypogaea L.) - Yan, Lei; Jin, Haotian; Raza, Ali; Huang, Yang; Gu, Deping; Zou, Xiaoyun (Frontiers in Plant Science, 2022)
As one of the most important and largest transcription factors, WRKY plays a critical role in plant disease resistance. However, little is known regarding the functions of the WRKY family in cultivated peanut (Arachis hypogaea L.). In this study, a total of 174 WRKY genes (AhWRKY) were identified from the genome of cultivated peanut. Phylogenetic analysis revealed that AhWRKY proteins could be divided into four groups, including 35 (20.12%) in group I, 107 (61.49%) in group II, and 31 (17.82%) in group III, and an 1 (0.57%) in group IVunclassified group. This division is further supported by the conserved motif compositions and intron/exon structures. All AhWRKY genes were unevenly located on all 20 chromosomes, among which 132 pairs of fragment duplication and 7 seven pairs of tandem duplications existed. Eighteen miRNAs were found to be targeting 50 AhWRKY genes. Most AhWRKY genes from some groups showed tissue-specific expression. AhWRKY46, AhWRKY94, AhWRKY156, AhWRKY68, AhWRKY41, AhWRKY128, AhWRKY104, AhWRKY19, AhWRKY62, AhWRKY155, AhWRKY170, AhWRKY78, AhWRKY34, AhWRKY12, AhWRKY95, and AhWRKY76 were upregulated in ganhua18 and kainong313 genotypes after R. solanacearum infection. Some Ten AhWRKY genes (AhWRKY34, AhWRKY76, AhWRKY78, AhWRKY120, AhWRKY153, AhWRKY155, AhWRKY159, AhWRKY160, AhWRKY161 and AhWRKY162) from group III displayed different expression patterns in Ralstonia solanacearum sensitive and resistant peanut genotypes infected with the Ralstonia solanacearum. Two AhWRKY proteins genes (AhWRKY76 and AhWRKY77) from group III obtained LRR domain, AhWRKY77 downregulated in twoboth cultivarsgenotypes, AhWRKY76 showed lower-higher expression in ganhua18 and higher expression in kainong313, AhWRKY76 and AhWRKY77 both targeted by ahy-miR3512, which may have an important function in peanut disease resistance. This study identified candidate WRKY genes with possible roles in peanut resistance against Ralstonia solanacearum infection. These findings not only contribute to our understanding of the novel role of WRKY family genes, but also provide valuable information for disease resistance in A. hypogaea.